2021
DOI: 10.1002/aoc.6399
|View full text |Cite
|
Sign up to set email alerts
|

Application of Janus Magnetic Nanoparticle Fe3O4@SiN functionalized with beta‐cyclodextrin in thymol drug delivery procedure: An in vitro study

Abstract: In this work, a novel drug delivery system was developed for thymol. Thymol is an herbal medicine that has low chemical reactivity. The drug delivery platform was Janus Magnetic Nanoparticle. The carrier's core‐shell structure was Fe3O4 nanoparticles (Fe3O4) as core and thin layer SiO2 (SiN) as a shell. The Fe3O4 nanoparticles were synthesized using the co‐precipitation method. A thin layer of SiO2 was covered on the surface of Fe3O4 nanoparticles. The whole Janus magnetic nanoparticle, Fe3O4@SiN, was function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Janus NPs are associated with two sides of a magnetic core and different functional materials. 169 , 170
Figure 3 Different coating structures for synthesis of MNCs and common shapes of the magnetic core. 171
…”
Section: Application Of Polymer In Stabilizing Magnetic Nanocompositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Janus NPs are associated with two sides of a magnetic core and different functional materials. 169 , 170
Figure 3 Different coating structures for synthesis of MNCs and common shapes of the magnetic core. 171
…”
Section: Application Of Polymer In Stabilizing Magnetic Nanocompositesmentioning
confidence: 99%
“…Janus NPs are associated with two sides of a magnetic core and different functional materials. 169,170 In a study by Wulandari et al, 172 Fe 3 O 4 NPs were fabricated by the ex-situ co-precipitation method and cross-linked with chitosan using tripolyphosphate/sulfate. The results from scanning electron microscopy (SEM) and X-ray diffraction (XRD) spectrum revealed that the increase of chitosan coating agent enhanced and declined the SEM size and crystallite size of the NPs, respectively.…”
mentioning
confidence: 99%
“…Fabrication of core–shell structures enables the selection of the core properties and provides the possibility for building suitable shell/shells to produce amazing multifunctional and multilayer materials for various applications including extraction, photocatalysis, solar energy, and hydrogen production . The challenges involved in the controlled fabrication of the iron-oxide-/silica-based magnetic core/shell structures is an important and ongoing research topic comprising efforts to enhance the magnetic materials’ stability, functionality and recycling potential for various applications. , The recycling and reuse of core–shell structures are important for the development of sustainable applications. , Most of the previous strategies for the formation and stabilization of Fe 3 O 4 -based magnetic core–shell structures focused on the functionalization of the shell and/or shells around the Fe 3 O 4 core. ,, These include Fe 3 O 4 @SiO 2 / Pr–N = Mo­[Mo5O 18 ], Fe 3 O 4 @SiO 2 @-SC, Fe 3 O 4 @SiO 2 @DMSA, Fe 3 O 4 @SiO 2 @HPG-OPPh 2 -PNP, Fe 3 O 4 @SiO 2 @rGO, Fe 3 O 4 @SiN/β-CD, Fe 3 O 4 @SiO 2 @IL-PMO/Pd, and Fe 3 O 4 –SiO 2 -2DMDPS . Therefore, in this research, we built a strategy for core stabilization and functionalization.…”
Section: Introductionmentioning
confidence: 99%
“… 63 , 64 Most of the previous strategies for the formation and stabilization of Fe 3 O 4 -based magnetic core–shell structures focused on the functionalization of the shell and/or shells around the Fe 3 O 4 core. 62 , 65 , 66 These include Fe 3 O 4 @SiO 2 / Pr–N = Mo[Mo5O 18 ], 67 Fe 3 O 4 @SiO 2 @-SC, 68 Fe 3 O 4 @SiO 2 @DMSA, 69 Fe 3 O 4 @SiO 2 @HPG-OPPh 2 -PNP, 70 Fe 3 O 4 @SiO 2 @rGO, 71 Fe 3 O 4 @SiN/β-CD, 72 Fe 3 O 4 @SiO 2 @IL-PMO/Pd, 73 and Fe 3 O 4 –SiO 2 -2DMDPS. 74 Therefore, in this research, we built a strategy for core stabilization and functionalization.…”
Section: Introductionmentioning
confidence: 99%
“…Although the delivery of Thymol via nanocarriers has been researched in the past, there is no proof that Thymol is delivered using niosomes. Taherkhani et al in 2021 have studied the application of Janus Magnetic Nanoparticle Fe3O4@SiN functionalized with beta-cyclodextrin in thymol drug delivery procedure; 31 however, only in vitro studies were conducted, no bioassays were performed, and the primary focus was on the characterization of the nanoparticle. Although polymeric nanoparticle modified by oleic acid (NPMO) was employed in another work by Karimi et al in 2019, 32 it was primarily focused on the angiogenic effects on rat’s olfactory ensheathing cells and it was concluded that in higher concentrations, the encapsulated thymol had shown more toxicity and resulted in increased the production of ROS.…”
Section: Introductionmentioning
confidence: 99%